Composition and chemical properties of the soils of the city of Santiago de Compostela, northwestern Spain. Issue 1 (8th June 2020) - Paradelo, Remigio; Herbón, Cecilia; Barral, María Teresa
Abstract: Urban soils are still insufficiently studied despite the relevance of their functions in the urban environment. The city of Santiago de Compostela (northwestern Spain) offers interesting opportunities for the study of urban soils because of its geological diversity and the variety of land use and vegetation. With the objective of increasing information about urban soils in Spain, we studied samples from 56 urban soils (0–20 cm) in this city, developed over different parent materials (granites, gneiss, schists, and amphibolites) and under several land uses (lawn areas, forested areas, urban allotment gardens, peri‐urban agricultural soils, and a green roof). The main physicochemical properties of the soils were analyzed, including bulk density, texture, pH, organic matter, cation exchange capacity, available P, and compounds of Fe and Al. The soils are coarse textured (dominant texture is sandy loam) and acidic (pH in water from 4.7 to 6.9), with moderate to high organic matter contents (13–137 g organic C kg −1 ). Cation exchange capacity ranges from 9 to 48 cmolc kg −1, with Ca as the most abundant exchangeable cation in most soils. Overall, the soils do not show several of the common features of other urban soils, such as alkalinity, high bulk density, or large amounts of artifacts, and their composition is very similar to their natural counterparts in the region. The conservation of these soils with a low degree of artificialization is essential because they can provide a wide range of ecosystem services. Core Ideas: The city of Santiago de Compostela has acidic, organic matter‐rich, sandy‐loam soils. Soils do not exhibit the most typical features of very anthropized urban soils. They are more similar to nearby natural and agricultural soils than to other urban soils.